First International Conference of Confederations of Epidemiological Associations (ICRMSW 2013) (Nepal Journal of Epidemiology, 2013)
It gives me immense pleasure to witness and participate in  the International Conference of research Methodology and Scientific Writing (ICRMSW-2013) organized by Mahatma Gandhi University and Confederation of Epidemiological Associations. It was the 1st Conference Confederation of Epidemiological Associations (CEA) being held at Kottayam, Kerala from December 20-22nd 2013. DOI: http://dx.doi.org/10.3126/nje.v3i4.9521